2020
DOI: 10.1177/1120672120953339
|View full text |Cite
|
Sign up to set email alerts
|

Redeployment of ophthalmologists in the United Kingdom during the Coronavirus Disease Pandemic

Abstract: Background: During the current coronavirus (COVID-19) pandemic, some ophthalmologists across the United Kingdom (UK) have been redeployed to areas of need across the National Health Service (NHS). This survey was performed to assess aspects of this process including training & education, tasks expected, availability of personal protection equipment (PPE) used and the overall anxiety of ophthalmologists around their redeployment. Method: Online anonymous survey around the existing guidance on safe redeploym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Mummery and Kipps (2020) advocates for flexibility, accounting for individuals’ circumstances, health risks and skills when considering redeployment strategy and staff well‐being. These findings were supported by Lim et al, (2020) who conducted a survey on ophthalmologists. They found that junior ophthalmologists were more comfortable with redeployment due to their more recent general medical experience compared with their senior colleagues.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Mummery and Kipps (2020) advocates for flexibility, accounting for individuals’ circumstances, health risks and skills when considering redeployment strategy and staff well‐being. These findings were supported by Lim et al, (2020) who conducted a survey on ophthalmologists. They found that junior ophthalmologists were more comfortable with redeployment due to their more recent general medical experience compared with their senior colleagues.…”
Section: Introductionsupporting
confidence: 77%
“…Following the H1N1 outbreak in Australia, one study was conducted using surveys investigating health workers’ absenteeism and sickness during the pandemic (Considine et al, 2011). Seven studies, surveys and articles were found relating to COVID‐19 redeployment, of those only one touched on the needs of non‐medically trained staff (Coughlan et al, 2020, Faderani et al, 2020, Johnston et al, 2020, Lim et al, 2020, Monroig‐Bosque et al, 2020, Mummery & Kipps, 2020 and Spiegelman et al, 2020) but the focus remained on medical doctors. Mummery and Kipps (2020) advocates for flexibility, accounting for individuals’ circumstances, health risks and skills when considering redeployment strategy and staff well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Staff wellbeing needs that required attention included accommodation, testing and family responsibilities (D’souza, Shetty, Apuri, & Moreira, 2020; George et al, 2020). Lim et al, (2020) reported that redeployed ophthalmologists’ anxiety reduced once their redeployment role began. This was attributed to receiving support from staff in the redeployed area, the sufficient availability of PPE, and adequate training.…”
Section: Resultsmentioning
confidence: 99%
“…No work had previously been undertaken on the effect of redeployment on ENT surgeons within the UK. Although analogous surgical subspecialties have published in the area, 7 , 11 , 12 it is vital as a subspecialty that we explore the path taken and additionally the potential role that trainee ENT surgeons offer within an emergency pandemic setting.…”
Section: Discussionmentioning
confidence: 99%